TASKS OF ENSURING INFORMATION AND PSYCHOLOGICAL SECURITY IN AN INFORMED SOCIETY - Parpiev M.T (European Journal of Humanities and Educational Advancements, 2023)
The article examines the increasing ideological influence of various information on the life and safety of people, the spiritual world of people in the information society, and the possibility of threats in cyberspace to have a serious negative impact on all areas of society